Umbilical cord blood-derived platelet-rich plasma as a coating substrate supporting cell adhesion and biological activities of wound healing - Thanh-Hai Tong; Xuan-Hai Do; Thanh-Thao Nguyen; Bich-Hanh Pham; Quang-Dung Le; Xuan-Hung Nguyen; Nhung Thi My Hoang; Thu-Huyen Nguyen; Nam Hoang Nguyen; Uyen Thi Trang Than (European Journal of Medical Research)
Abstract Background Platelet-rich plasma (PrP) is a blood derivative with positive roles in regenerative medicine, particularly in wound healing. Evidence has been reported for using peripheral blood-derived PrP in disease treatments, but umbilical cord blood (UCB)-derived PrP remains limited. Thus, we investigate the roles of UCB-derived PrP in cellular behaviours in vitro and in wound healing in vivo models. Methods We used 2D and 3D cell culture models to investigate the role of UCB-derived PrP gels in stimulating the attachment, proliferation, migration, and spheroid formation of umbilical cord-derived mesenchymal stem cell (UCMSC) and human dermal fibroblast (hFB). In addition, immunoassay and PCR were used to understand the enrichment of growth factors in UCB-derived PrP and the change of ECM genes in PrP-treated cells. Finally, a rat model was used to investigate the cutaneous wound healing process. Results UCB-derived PrP gels were enriched with platelet-derived growth factor-BB (PDGF-BB) (3394.1 ± 2658.3 pg/mL), vascular endothelial growth factor-A (VEGF-A) (282.0 ± 53.0 pg/mL), hepatocyte growth factor (HFG) (762.7 ± 117.5 pg/mL), and fibroblast growth factor 2 (FGF-2) (17.734 ± 8 pg/mL). In addition, these UCB-derived PrP gels promoted cell attachment (> 154 % and > 117 % for UCMSCs and hFBs, respectively), proliferation (UCMSCs > 121 % and hFBs > 117 % at all time points), migration increased by 27 % and 26 % for UCMSCs and hFBs, and spheroid formation and fusion compared to the control. UCB-derived PrP gels also induced different expression of ECM genes, including COL1, COL3, HAS1, HAS2, HAS3, and ENL, in both UCMSCs and hFBs. Finally, this product from UCBs could enhance the wound healing process in excised skin rat models by reducing the wound area by 80 % compared to 27 % in controls after 14 days. Conclusions UCB-derived PrP gels facilitate cell behaviours in vitro, including cell adhesion, growth, and migration. In addition, in animal models, UCB-derived PrP reduced the wound healing time and enhanced the completion of skin tissues by increasing granulation tissue formation and reducing neutrophils at wound sites. These UCB-derived PrP gels will be used to support spheroid formation that will be used as biomaterials for 3D printing, engraftment, and wound healing treatment.